Composition and Structure of the Vegetation in Asola-Bhati Wildlife Sanctuary of National Capital Territory, Delhi - Naithani, H. B. (Indian Forester, 2015)
A detailed study of the composition of vegetation in the Asola-Bhati sanctuary of NCT of Delhi was done during 2001 to 2003 and 2010 to know the density, richness and regeneration of tree species along with the shrubs, herbs, climbers, grasses and sedges. The results are striking and revealed that the quarry pits of Bhati mines holds the rich wealth of plants,as the area encompassing 16 tree species, 12 shrub species, 37 herb species, 9 climbers, 18 grass species, 3 sedge species and a bryophyte after a fellow period of 19 years since 1991 - 1992 before that was known for excessive mining for building making materials (Badarpur). Wrightia arborea a tree is reported for the first time from NCT Delhi. The quantification of vegetation revealed good density and frequency which is at par to the other similar forests over the globe. The present study will be a base line data for future study of Delhi.